2010
DOI: 10.1016/j.jsbmb.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and hyperandrogenism in women with polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a very common endocrine disorder characterized by chronic anovulation, clinical and/or biochemical hyperandrogenism, and/or polycystic ovaries. But most experts consider that hyperandrogenism is the main characteristic of PCOS. Several theories propose different mechanisms to explain PCOS manifestations: (1) a primary enzymatic default in the ovarian and/or adrenal steroidogenesis; (2) an impairment in gonadotropin releasing hormone (GnRH) secretion that promotes luteal horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
214
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(227 citation statements)
references
References 154 publications
(148 reference statements)
5
214
1
7
Order By: Relevance
“…These are areas of unresolved understanding with regard to PCOS. Although, proposed mechanisms for insulin induced reproductive abnormalities include inappropriate ovarian steroidogenesis, excessive LH secretion and abnormalities in glucose uptake [18], in effect increased insulin does not appear to govern gonadotropin secretion directly. PCOS women treated with pioglitazone demonstrated improved insulin sensitivity without alterations in LH pulse frequency or amplitude, or gonadotropin responses to GnRH [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are areas of unresolved understanding with regard to PCOS. Although, proposed mechanisms for insulin induced reproductive abnormalities include inappropriate ovarian steroidogenesis, excessive LH secretion and abnormalities in glucose uptake [18], in effect increased insulin does not appear to govern gonadotropin secretion directly. PCOS women treated with pioglitazone demonstrated improved insulin sensitivity without alterations in LH pulse frequency or amplitude, or gonadotropin responses to GnRH [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although, it is widely accepted that hyperinsulinemia due to insulin resistance causes hyperandrogenism, studies undertaken with reverse aim showed that testosterone administration caused insulin resistance in skeletal muscle of female rats and in adipocytes of women in vitro [20]. On the other hand, the results of some studies suggested that these two conditions might be two separate entities [18]. The absence of significant association between hyperandrogenemia and insulin resistance in some recent studies have further supported this view [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SREBP-1 is a transcription factor responsible for the biosynthesis of various fatty acids (Shao & Espenshade 2012). Insulin regulates SREBP activation and translocation from cytoplasm into the nucleus through PI3K/Akt and mammalian target of rapamycin (mTOR) signaling pathway (Baptiste et al 2010).…”
Section: Insulinmentioning
confidence: 99%
“…It is due to a combination of genetic and environmental factors. A dysfunction of the hypothalamicpituitary-ovarian or adrenal axis was proposed to be the cause of hyperandrogenemia in women with PCOS (Hall et al 1998, Baptiste et al 2010. Risk factors for the…”
Section: Introductionmentioning
confidence: 99%